De-Radicalization through Prophetic Education in High School - Mat Solikhin (Nadwa: Jurnal Pendidikan Islam, 2020)
This research analyze the management of de-radicalization through the prophetic education, case study in State Senior High School (SMAN 1) and State Islamic High School (MAN 1) Kendal, Jawa Tengah, Indonesia. The research used qualitative method. Data collection technique in this research are observation, interview and documentation. The results showed; 1) the humanizing human beings is the key in organizing the radicalism ideological movement in prophetic education in Indonesia. Meanwhile, in the relationship between religious values and national culture, it must provide space for pluralism and multiculturalism 2) the process of de-radicalization in prophetic education in Indonesia through prophetic values in Islamic Civilization History (Sejarah Kebudayaan Islam, SKI), Al-Qur'an, Hadith, Akidah Akhlaq, and various extra-curricular activities. Based on the evaluation conducted most of students are already good in showing anti-radicalism attitude.AbstrakPenelitian ini menganalisis pengelolaan de-radikalisasi melalui pendidikan kenabian, study kasus di Sekolah Menengan Atas 1 (SMAN 1) dan Madrasah Aliyah Negeri 1 (MAN 1) Kendal, Jawa Tengah, Indonesia. Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Hasilnya menunjukkan; 1) bahwa memanusiakan manusia adalah kunci dalam menata gerakan ideologi radikalisme dalam pendidikan profetik di Indonesia. Sedangkan dalam relasi antara nilai-nilai agama dan budaya bangsa maka harus memberi ruang pada pluralisme dan multikulturalisme. 2) proses deradikalisasi dalam pendidikan kenabian di Indonesia melalui nilai-nilai kenabian dalam SKI, Al-Qur'an, Hadits, Akidah Akhlaq, dan berbagai kegiatan ekstra kurikuler. Berdasarkan evaluasi yang dilakukan, sebagian besar siswa sudah bagus dalam menunjukan sikap anti radikalisme.